Tradisi Massafa’ Suku Bugis Di Desa Sumber Jaya Kabupaten Banyuasin - Merianti; Amilda; Fitriah (Program Studi Sejarah Peradaban Islamm UIN Raden Fatah Palembang, 2024)
Islamic religious values have a big influence on the social life of the Bugis-Makassar and Makassar communities in South Sulawesi. Apart from that, this research also shows that in the history of South Sulawesi there have been political and social changes that have influenced the lives of the Bugis-Makassar tribe, but interpersonal ties and the process of cultural acculturation still play an important role. people's lives. The Makassar Bugis Tribe in South Sulawesi and its History, Culture, Traditions and Rituals. This research also explains the importance of educating children, as well as the religious and social values contained in the Massafa' tradition. Apart from that, this research also discusses traditional cakes from the Bugis and Makassar tribes, as well as the philosophical values associated with these cakes.